NEGATIVE EMBODIMENT OF THE PROTAGONIST’S INTERNAL CONFLICT IN NANG SYAMSUDIN’S NOVEL MENGURAI RINDU - Indah Lestari; Andang Suhendi (JOURNAL OF LANGUAGE, 2020)
This study talks about the protagonist’s internal conflict in Mengurai Rindu written by Nang Syamsudin. This study only focuses on the negative embodiment of the Protagonist, internal conflict, and the positive one is not discussed. The theory used in this study is the theory of psychological conflicts; while, the method is descriptive method. The negative embodiment of the protagonist’s internal conflict which can be found in the novel are sadness, and disappointment. First, the protagonist often feels sad. Such feeling falls down on the protagonist’s mind. There are some characters who cause the protagonist’s sadness. Even, the protagonist feels distressed because of improper treatments from the other characters. Her sadness proves that there is an internal conflict which happens to her. The second is disappointment. Besides sadness, the protagonist also looks disappointed with those characters. Their reaction to the protagonist leaves her disappointment. In conclusion, some characters contribute conflicts for the protagonist. It can be said that external factors can result in internal conflict to anyone.